A Genre Analysis of Research Article Abstracts in Forensic Linguistics - Isaac Essoun; Dorah Kwakyewaa Adusei; Emmanuel Mensah Bonsu (Pascasarjana Universitas Negeri Makassar, 2022)
As a key genre in the academic discourse community, research articles (RA) have enjoyed great popularity over the years. A key component of the RA is the RA abstract. Its essence is seen in its objective of giving an overview of the study. Given the dearth of genre analysis in the Forensic Linguistics discipline, the study aimed at exploring the move structure and lexico-grammatical features of RA abstracts published in Forensic Linguistics. Adopting Hyland’s five-move model for analysing abstracts, the study randomly sampled ninety (90) RA abstracts from three different Forensic Linguistics journals. Guided by Hüttner’s classification model, the study identified the Purpose move as an obligatory move with 100%. It was revealed that the abstracts follow the semi-linear move sequence, i.e., M1>M2>M3>M4, which was the preferred pattern. The highest textual space was allocated to the Introduction move, and the average number of words in the abstract was 264. With the linguistic realisation of the moves, the present verb tense was preferred, occurring frequently in the Introduction, Purpose, Product and Conclusion moves. Adjunct adverbials were found to dominate the Introduction move, while disjunct adverbials never occurred in any of the moves. The study has insightful implications for language pedagogy, knowledge in the field of Forensic linguistics, and further research.